M268 The Ipf Diagnosis – Communicating A Life Sentence. (10th November 2014) - Wibberley, S; Ochiai, Y; Pitt, R; Mathieson, N
Abstract : Background: The aim was to explore the patients' emotional experience of receiving a diagnosis of IPF. Methods: Market research was conducted with an independent agency. Patients with IPF were asked to record a personal account of their experience on a hand-held camera. Face to face interviews with patients were conducted in their home. Carers were also interviewed to add an alternative perspective. Results: The sample included 13 male and 3 female patients with IPF. Patients with lung function impairment of all severities were included, five patients were treated with oxygen therapy and another had received a lung transplant. There was a national spread geographically throughout England. There is a fine balance to providing information and patients can benefit from an individually tailored approach. Too much information at the start can be overwhelming. Too little information can leave the individual uncertain about how to deal with their future. Gaps that were identified focused on the practicalities of living with IPF, including social care. There was a high expectation for their physician to explain the trigger for developing IPF. Patients felt a blame culture exists, whereby others felt that IPF is self-inflicted, like COPD, particularly when a patient was taking oxygen therapy. Patients may be left with feelings of anger at missed opportunities and concern for lost years of intervention and appropriate palliative care support. Conclusions: The diagnosis of IPF is a devastating one, which can be challenging to manage. Carers, patient groups and expert support at diagnosis were found to be invaluable to patients during this time.